Cannabis in Acute Injury Rehabilitation: Analgesic Efficacy, Functional Outcomes and Dependency Risks - Polok, Sebastian; Talaska, Justyna; Wasilewska, Małgorzata; Pietrzak, Krzysztof; Demel, Karol (Quality in Sport, 2025)
Background: Musculoskeletal injury rehabilitation is challenged by inadequate pain management using opioids and NSAIDs, which pose risks of addiction, side effects, and delayed healing. Cannabis has emerged as a potential analgesic, yet its efficacy, safety, and impact on functional recovery in acute injuries remain unclear, particularly for athletes. Purpose of Research: To evaluate the role of cannabis in acute injury rehabilitation, focusing on analgesic efficacy, functional outcomes, addiction risks, and implications for athletic recovery. Materials and Methods: A systematic review of PubMed and Google Scholar (2015–present) identified 24 studies (RCTs, observational studies, meta-analyses) assessing cannabis in acute injury rehab. Inclusion criteria prioritized pain scores (VAS/NRS), functional metrics (mobility, strength), and dependency rates (CUDIT). Non-English articles and animal studies were excluded. Basic Results: Cannabis demonstrated moderate analgesic efficacy, with 30% pain reduction vs. placebo in acute musculoskeletal injuries. Low-dose THC matched opioid efficacy with fewer side effects, while CBD showed anti-inflammatory effects (22% IL-6 reduction). Functional improvements in mobility and therapy adherence were noted, but psychoactive effects (sedation, cognitive impairment) and a 10–15% cannabis use disorder (CUD) prevalence were reported. Discrepancies emerged between subjective pain relief and objective biomarkers. Conclusions: Cannabis may offer short-term analgesic and functional benefits in acute injury rehab but requires careful risk-benefit assessment due to addiction potential, cognitive side effects, and variable dosing responses. Standardized guidelines, athlete-specific protocols, and multidisciplinary monitoring are critical to optimize therapeutic outcomes. Future research should prioritize long-term safety, dosing standardization, and sport-specific functional impacts.